Gender Inequality and Trade - Christian Spielmann; Matthias Busse (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
The paper empirically explores the international linkages between gender inequality and trade flows of a sample of 92 developed and developing countries. The focus is on comparative advantage in labour-intensive manufactured goods. The results indicate that gender wage inequality is positively associated with comparative advantage in labourintensive goods, that is, countries with a larger gender wage gap have higher exports of these goods. Also, gender inequality in labour force activity rates and educational attainment rates are negatively linked with comparative advantage in labour-intensive commodities.
Keywords: J80; F11; F16; J70; 330; Gender Inequality; Trade; Comparative Advantage